Comparative analysis of dentinal tubule penetration: effects of irrigation activation methods and root canal sealers: in-vitro study - Yagmur Kilic; Mustafa Mert Tulgar; Emrah Karataslioglu; Tugba Turk (BMC Oral Health)
Abstract Background To seal the entire root canal system is the main objective of root canal treatment. While obturating the main root canal, sealing the dentinal tubules that are known to open to the root canal system plays an important role. Present study investigated the dentine tubule penetration of different root canal sealers combined with different irrigation activation methods using an in-vitro model. Methods The root canal preperation of the 144 samples was completed using the Ni-Ti rotary K7 system. All samples were divided into 3 groups (n = 48) according to irrigation activation(sonic activation, passive ultrasonic activation and needle activation). Activation groups were divided into 4 subgroups (n = 12) according to the root canal sealer used (GuttaFlow, Bioroot RCS, AH Plus Bio, AH Plus Jet). Horizontal sections taken at the 6 mm level from the apex were examined with CLSM to evaluate the maximum penetration depth and penetration percentage. The normal distribution of numerical variables was assessed using the Shapiro-Wilk normality test. The homogeneity of variances among groups was analyzed with the Levene test. Comparisons for log penetration depth and penetration percentage were made using two-way analysis of variance. Results In terms of penetration area, sonic activation showed significantly higher values compared to needle activation, while ultrasonic activation did not differ significantly from these two methods (p = 0.048). The Bioroot RCS group had a significantly higher penetration area percentage compared to the GuttaFlow group, with no significant differences among the other sealer groups (p = 0.017). In the AH Plus Jet group, the maximum penetration depth with ultrasonic activation was found to be significantly higher compared to needle activation (p = 0.036). Conclusion It was found that sonic activation and BioRoot RCS were superior in dentinal tubule penetration compared to other groups. All the groups have demonstrated penetration. It is believed that effective dentinal tubule penetration can be achieved with continuous irrigation, properly applied activation systems, and adherence to manufacturer instructions when using root canal sealers.